2022
DOI: 10.3389/fpls.2022.1021617
|View full text |Cite
|
Sign up to set email alerts
|

Methylation level of potato gene OMT30376 regulates tuber anthocyanin transformations

Abstract: After anthocyanin synthesis, a variety of anthocyanin compounds are produced through further methylation, glycosylation, and acylation. However, the effect of the potato methylase gene on anthocyanin biosynthesis has not been reported. Red and purple mutation types appear in tubers of the potato cultivar ‘Purple Viking’ with chimeric skin phenotypes. In this study, transcriptome and anthocyanin metabolome analyses were performed on skin of Purple Viking tubers and associated mutants. According to the metabolom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…LTPs were first observed in spinach ( Spinacea oleracea L.) leaves, maize ( Zea mays L.) coleoptiles, and barley ( Hordeum vulgare L.) aleurone (Wei & Zhong, 2014 ). It was reported that the LTP genes were highly adaptable to stress in maize (Noonan et al, 2017 ), rice ( Oryza sativa L.) (Lin et al, 2017 ), cotton ( Gossypium hirsutum L.) (Zhang, Zhao, et al, 2022 ), wheat ( Triticum aestivum L.) (Fang et al, 2020 ), potato (Shang et al, 2022 ), Arabidopsis ( Arabidopsis thaliana [L.] Henyh.) (Zou et al, 2013 ), and other crops.…”
Section: Introductionmentioning
confidence: 99%
“…LTPs were first observed in spinach ( Spinacea oleracea L.) leaves, maize ( Zea mays L.) coleoptiles, and barley ( Hordeum vulgare L.) aleurone (Wei & Zhong, 2014 ). It was reported that the LTP genes were highly adaptable to stress in maize (Noonan et al, 2017 ), rice ( Oryza sativa L.) (Lin et al, 2017 ), cotton ( Gossypium hirsutum L.) (Zhang, Zhao, et al, 2022 ), wheat ( Triticum aestivum L.) (Fang et al, 2020 ), potato (Shang et al, 2022 ), Arabidopsis ( Arabidopsis thaliana [L.] Henyh.) (Zou et al, 2013 ), and other crops.…”
Section: Introductionmentioning
confidence: 99%